A Snapshot of Policy-Oriented Projects Based on Administrative Benefits Data in the UK - Ghelani, Deven; Uraz, Juliet-Nil; Torres Cortés, Francisca (International Journal of Population Data Science, 2025)
Objectives We present research projects conducted linking administrative benefits data held by local authorities with other datasets. Leveraging the richness of this individual-level monthly data, we demonstrate its potential to support local authorities’ statutory duties and reveal the role played by non-take-up in vulnerable households’ trajectories. Methods Drawing on our experience working with over 40 local authorities, we showcase projects linking administrative benefits data with local datasets, such as adult and children’s social care records, and external sources, including legal services, water companies, and healthcare providers. We assess the overlap between cohorts in administrative benefits data and low-income populations in external datasets. We outline the key variables included, the legal gateways enabling data sharing, and the challenges of designing (quasi-) experimental setups to evaluate interventions. Administrative benefit data sources include: the Council Tax Reduction Scheme, the Single Housing Benefits Extract and the Universal Credit Data Share. Results Administrative benefits data offer a dynamic snapshot of a household’s financial situation. Local authorities can proactively use and share this data with external processors to fulfil their statutory duties if a legal gateway allows. Identifying households at risk of cash shortfalls before crisis point enables targeted interventions for local welfare schemes and homelessness prevention. By comparing benefit eligibility and uptake, local authorities can run data-driven outreach campaigns and evaluate their impacts. These research projects reveal how interventions – such as legal advice, uptake campaign letters, autoenrollment in social tariffs, or referrals to social care – affect individual financials situations in a timely manner. We analyse when impacts manifest and their duration, offering insights into how administrative benefits data can support the design and evaluation of policy interventions. Conclusions Local authorities routinely process longitudinal benefits data, providing real-time insights into low-income households’ socioeconomic situations. Despite its potential for policy-oriented research, this resource remains underutilized. Unlocking its value through responsible data sharing and linkage can enhance evidence-based policymaking, improving support for vulnerable populations.